SOCIALIZATION OF SIMPLE BOOKKEEPING TECHNIQUES WITH FINANCIAL REPORT PREPARATION TRAINING TO MOTHERS IN THE DEPOK AREA - Indawati , Indawati; Anggraini , Anggun; Sunarto , Ading (International Journal of Engagement and Empowerment (IJE2), 2026)
This Community Service Program (PKM) aims to improve financial literacy among mothers in the Depok area through the dissemination of simple bookkeeping techniques and training in preparing financial reports. This activity is motivated by the low financial record-keeping skills of households and small businesses run by mothers, which often makes it difficult to manage cash flow, assess profits, and plan for long-term needs. The implementation method includes interactive counseling, simulations of recording daily transactions, and direct practice in preparing simple financial reports based on income and expenses. Participants are trained to understand the importance of financial record-keeping, recognize the components of financial reports, and be able to prepare reports that can be used as a basis for economic decision-making for families and micro-businesses. The expected results of this activity are increased financial awareness, the formation of simple financial record-keeping habits, and the ability of mothers to prepare more structured financial reports. Thus, this PKM is expected to make a real contribution to supporting family economic independence and community empowerment in Depok.